Temperature-resistant and salt-resistant polyether sulfonate oil-displacing agent and preparation method thereof

By preparing amphiphilic FAU nanocrystals and polyether sulfonate compound, the problems of difficulty in synthesis of polymers, low surfactant and low efficiency in the existing chemical oil flooding technology have been solved, and the temperature and salt resistance and salt resistance have been significantly improved and the oil recovery rate have been improved.

CN119570471AActive Publication Date: 2025-03-07SHENYANG ZHONGKE ENVRIONMENTAL ENG TECH DEV CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510138434.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-07
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

The existing chemical oil flooding technology has problems such as difficulty in synthesis of polymers, low surfactant interference efficiency, and chromatographic separation of composite flooding, which limits the on-site application of chemical flooding, and urgently needs to study new technologies to improve recovery rates.

Method used

By preparing amphiphilic FAU nanocrystals, combining polyether sulfonate, a high-yield FAU nanocrystals with high yields were directly synthesized by one-step method, and on this basis, FAU nanocrystal fluid with amphiphilic properties was prepared to optimize the performance of the system and improve its temperature and salt resistance.

Benefits of technology

The temperature and salt resistance of polyether sulfonate is significantly improved, the strength of the droplet interface film and the interface viscoelasticity of the emulsion is enhanced, the coalescence of emulsion droplets is delayed, and the stability of the emulsion and oil recovery rate is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570471A_ABST
    Figure CN119570471A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oil-displacing agents, in particular to a temperature-resistant and salt-resistant polyether sulfonate oil-displacing agent and a preparation method thereof, and the temperature resistance and the salt resistance are enhanced by compounding amphiphilic FAU nanocrystals and polyether sulfonate. The compound system has good emulsifying ability, dispersion stability and mobility control ability, and can significantly improve the oil recovery rate. The hydrophobically modified FAU zeolite enhances the affinity of an oil phase, improves the oil displacement efficiency, and reduces the influence on the environment at the same time. The system is biodegradable, meets the requirements of environmental protection and sustainable development, and provides a new scheme for an oil field chemical oil displacement technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil displacement agents, in particular to a temperature-resistant and salt-resistant polyether sulfonate oil displacement agent and a preparation method thereof. Background Art

[0002] Oil is known as the "blood of industry" and occupies a large part of the energy used by humans. It has an extremely important strategic position. After the secondary oil recovery and water injection stage, the recovery rate of most oil fields is less than 50% (Du Chunbao, Cai Yuxiu, Yan Yongli, et al. Research Progress of New Chemical Oil Flooding Technology [J]. Modern Chemical Industry, 2022, 42 (6): 35.39.), and a large amount of crude oil remains in the underground reservoir. This part of crude oil is difficult to displace by water injection. The shortage of oil resources is becoming increasingly severe. Improving crude oil recovery is an urgent problem to be solved. Improving oil recovery is also called tertiary oil recovery. It is divided into chemical flooding, miscible flooding, thermal recovery and microbial flooding. Among them, chemical flooding has the most mature application and has broad development prospects. Chemical flooding refers to adding a certain amount of chemical reagents to the injection fluid. Common chemical flooding can be divided into: polymer flooding, surfactant flooding and composite flooding. Polymer flooding is the most widely used method because of its outstanding effects in improving mobility ratio and adjusting profile. However, it is difficult for the synthesis of polymers to combine excellent properties such as temperature resistance and salt tolerance and improved mobility ratio. Surfactant flooding improves oil recovery by reducing interfacial tension and changing wettability, but surfactant sweep efficiency is low and adsorption loss is large. Composite flooding can coordinate the oil displacement mechanism of polymer and surfactant, with high displacement efficiency, but there is chromatographic separation, which affects oil recovery efficiency. In summary, the chemical flooding currently used on a large scale has certain defects, which limits its on-site application. It is urgent to study new technologies to improve oil recovery.

[0003] Nanoparticles are small in size and have high surface activity and large specific surface area. Laboratory studies have shown that nanomaterials can be used to improve oil recovery. Nanoparticles can be dispersed in water or oil-water mixed systems to drive oil alone, or they can be used in combination with surfactants or polymers. The preparation process of nanomaterials is complex and the productivity is low, making them difficult to apply in industry. In addition, nanoparticles also face challenges in dispersion and stability when used in combination with surfactants. In the compound system, the interaction between nanoparticles and surfactants may lead to complex changes in surface activity, viscosity and conductivity, affecting the performance of the system. The adsorption and arrangement of nanoparticles at the gas-liquid interface and the effect of surfactants on their adsorption are key factors. The adsorption process of nanoparticles needs to overcome certain adsorption energy barriers, such as electrostatic repulsion. In addition, the irreversible adsorption characteristics of nanoparticles lead to an increase in their adsorption density during droplet shrinkage, thereby affecting surface tension and foam stability. The addition of surfactants changes the wettability of nanoparticles, thereby affecting their adsorption behavior at the gas-liquid interface, which is crucial for the stability of foams or emulsions. However, the current preparation methods of nanoparticles are complex and the low yield also restricts their development in the field of oil displacement agents. Summary of the invention

[0004] The object of the present invention is to provide a heat-resistant and salt-resistant polyether sulfonate oil-displacing agent and a preparation method thereof, which has a more stable dispersion ability by preparing amphiphilic FAU nanocrystals, and the nanofluid dispersed by using amphiphilic FAU nanocrystals has long-term stability, and has a large specific surface area compared to the nanoparticles modified by a single functional group, and has a stronger ability to reduce interfacial tension and change the surface wettability of reservoir rocks, and has a high application potential in improving crude oil recovery. The lipophilic FAU nanocrystals prepared by the one-step method of the present invention have high crystallinity, good dispersibility and high yield, and the amphiphilic FAU nanocrystals prepared on this basis still maintain a stable crystal structure, and the performance of the system is optimized by finely regulating the ratio and interaction of the amphiphilic FAU nanocrystals and the polyether sulfonates when used in combination, and further improving its heat resistance and salt resistance.

[0005] In order to solve the above technical problems, the present invention provides a temperature-resistant and salt-resistant polyether sulfonate oil-displacing agent and a preparation method thereof.

[0006] To achieve the above object, the present invention provides the following technical solution: a temperature-resistant and salt-resistant polyether sulfonate oil-displacing agent and a preparation method thereof, comprising the following steps: Step 1: adding a silane hydrophobic template to white carbon black and mixing them evenly, adding a sodium aluminate aqueous solution prepared by dissolving sodium aluminate in water, stirring evenly to obtain a gel-like semi-liquid mixture, wherein the above raw materials are calculated by mass ratio of white carbon black: sodium aluminate: silane hydrophobic template: water = 1:0.5-2:0.8-2:5-15; Step 2: crystallizing the mixture under steam-assisted conditions to obtain a crystalline product; Step 3: washing, drying and calcining the crystal product in sequence to obtain lipophilic FAU nanocrystals in one step; Step 4: Place a sodium hydroxide aqueous solution (concentration 1-10 g / L) into a round-bottom flask, add ethanol and mix well, add lipophilic FAU nanocrystals, and stir at 70-100°C for 2-5 hours to obtain an amphiphilic FAU nanocrystal fluid. The above raw materials are calculated by mass ratio: lipophilic FAU nanocrystals: sodium hydroxide aqueous solution: ethanol = 1:60-100:10-25; Step 5: Add the amphiphilic FAU nanocrystalline fluid, polyether sulfonate and water into a round-bottom flask and stir at 70-80° C. for 2-5 hours to obtain a temperature-resistant and salt-resistant polyether sulfonate oil displacement agent. The above raw materials are calculated by mass ratio of amphiphilic FAU nanocrystalline fluid: polyether sulfonate: water = 100:1.5-20:0.5-200.

[0007] Furthermore, the silane hydrophobic template agent is one of 3-aminopropyltriethoxysilane and (3-(2-aminoethyl)aminopropyl)triethoxysilane.

[0008] Furthermore, the polyether sulfonate is one of sodium octylphenol polyoxyethylene ether sulfonate and disodium lauryl alcohol polyoxyethylene ether sulfosuccinate.

[0009] Furthermore, step 2, crystallizing the mixture under steam-assisted conditions, specifically includes the following steps: transferring the mixture into an open glass container, and then transferring the glass container into a hydrothermal reactor lining, adding deionized water to the reactor lining whose mass is 0.5 to 2 times the mass of the mixture, and preventing water outside the glass container from entering the glass container; crystallizing the mixture under steam-assisted conditions at a temperature of 60 to 100° C. for 6 to 12 hours.

[0010] Furthermore, the calcination temperature in step 3 is 120-300° C., and the calcination time is 3-6 hours.

[0011] The present invention provides a heat-resistant and salt-resistant polyether sulfonate oil-displacing agent and a preparation method thereof. By compounding amphiphilic FAU nanocrystals with polyether sulfonates, the temperature resistance and salt resistance of polyether sulfonates are significantly improved. In the preparation process, we adopted a one-step method to directly synthesize high-yield lipophilic FAU nanocrystals, and on this basis, prepared FAU nanocrystalline fluids with amphiphilic properties without destroying the crystal structure. This amphiphilic FAU nanocrystalline fluid can form a stable adsorption layer at the oil-water interface, enhance the strength of the droplet interface film, and improve the interfacial viscoelasticity of the emulsion. At the same time, its amphiphilic nature also helps to construct a three-dimensional network structure in the bulk phase, enhance the bulk viscosity of the emulsion oil displacement system, effectively delay the coalescence of the emulsion droplets, and greatly improve the stability of the emulsion. As a surfactant, polyether sulfonates not only further enhance this stability, but also significantly improve the salt resistance and high temperature resistance of the oil-displacing agent due to their strong hydrophilicity. This composite system, with its excellent emulsification ability, good dispersion stability and enhanced mobility control ability, is conducive to improving the sweep coefficient, thereby significantly improving the oil recovery rate. After the hydrophobic modification of FAU zeolite, its surface properties are adjusted, the affinity with the oil phase is enhanced, and it plays a greater role in the oil recovery process. This modified zeolite can more effectively adsorb and transfer oil molecules, while reducing the flow resistance of the water phase, further improving the oil recovery efficiency. The combination of polyether sulfonate and hydrophobically modified FAU zeolite not only improves the performance of the oil displacement agent in the reservoir, but also reduces the impact on the ecological environment due to its environmental friendliness. The biodegradability and low interference with the reservoir environment of this composite system make it meet the requirements of modern oilfield development for environmental protection and sustainable development while improving oil recovery. Therefore, the synergistic effect of polyether sulfonate and hydrophobically modified FAU zeolite not only shows high efficiency in technology, but also shows its important value in saving resources and protecting the environment, providing new ideas and solutions for the development of oilfield chemical flooding technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is the XRD diagram of the temperature-resistant and salt-resistant polyether sulfonate oil-displacing agent prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0013] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0014] The following examples specifically illustrate a heat-resistant and salt-resistant polyether sulfonate oil-displacing agent and a preparation method thereof provided by the present invention.

[0015] Example 1

[0016] Step 1: Add 3-aminopropyltriethoxysilane to white carbon black and mix them evenly, add a sodium aluminate aqueous solution prepared by dissolving sodium aluminate in water, and stir evenly to obtain a gel-like semi-liquid mixture, wherein the above raw materials are calculated by mass ratio of white carbon black: sodium aluminate: 3-aminopropyltriethoxysilane: water = 1:0.95:1:5; Step 2: The mixture is transferred into an open glass container under steam-assisted conditions, and the glass container is then transferred into a hydrothermal reactor liner, deionized water is added into the liner, and the mass of the deionized water is 1 times the mass of the mixture, and water outside the glass container is prevented from entering the glass container; the mixture is crystallized at a temperature of 85° C. under steam-assisted conditions for 10 hours to obtain a crystalline product; Step 3: washing the crystal product, drying and calcining the product in sequence, at a calcination temperature of 250° C. for 5 hours, to obtain lipophilic FAU nanocrystals in one step; Step 4: Place a sodium hydroxide aqueous solution (concentration 1.25 g / L) into a round-bottom flask, add ethanol and mix well, add lipophilic FAU nanocrystals, and stir at 85°C for 3 hours to obtain an amphiphilic FAU nanocrystal fluid. The above raw materials are calculated by mass ratio: lipophilic FAU nanocrystals: sodium hydroxide aqueous solution: ethanol = 1:80:19; Step 5: Add the amphiphilic FAU nanocrystalline fluid, sodium octylphenol polyoxyethylene ether sulfonate and water into a round-bottom flask and stir at 80° C. for 3 hours to obtain a heat-resistant and salt-resistant polyether sulfonate oil displacement agent. The above raw materials are calculated by mass ratio: amphiphilic FAU nanocrystalline fluid: sodium octylphenol polyoxyethylene ether sulfonate: water = 100:2.5:1.

[0017] The amphiphilic FAU nanocrystal fluid prepared in step 4 was filtered and dried to obtain amphiphilic FAU nanocrystals for XRD test. Figure 1 As shown, the product is well crystallized without an amorphous phase, with the first peak at 6.09°, and the remaining peaks correspond to PDF#12-0246 in jade, proving that the sample is FAU zeolite.

[0018] Example 2

[0019] Step 1: adding 3-aminopropyltriethoxysilane to white carbon black and mixing them evenly, adding a sodium aluminate aqueous solution prepared by dissolving sodium aluminate in water, stirring evenly to obtain a gel-like semi-liquid mixture, wherein the above raw materials are calculated by mass ratio of white carbon black: sodium aluminate: 3-aminopropyltriethoxysilane: water = 1:1.25:1.1:1; Step 2: The mixture is transferred into an open glass container under steam-assisted conditions, and the glass container is then transferred into a hydrothermal reactor liner, deionized water is added into the liner, and the mass of the deionized water is 1 times the mass of the mixture, and water outside the glass container is prevented from entering the glass container; the mixture is crystallized at a temperature of 90° C. under steam-assisted conditions for 8 hours to obtain a crystalline product; Step 3: washing the crystal product, drying and calcining the product in sequence, at a calcination temperature of 250° C. for 5 hours, to obtain lipophilic FAU nanocrystals in one step; Step 4: Place a sodium hydroxide aqueous solution (concentration 1.53 g / L) into a round-bottom flask, add ethanol and mix well, add lipophilic FAU nanocrystals, and stir at 75°C for 3 hours to obtain an amphiphilic FAU nanocrystal fluid. The above raw materials are calculated by mass ratio: lipophilic FAU nanocrystals: sodium hydroxide aqueous solution: ethanol = 1:70:29; Step 5: Add the amphiphilic FAU nanocrystalline fluid, sodium octylphenol polyoxyethylene ether sulfonate and water into a round-bottom flask and stir at 85° C. for 3 hours to obtain a heat-resistant and salt-resistant polyether sulfonate oil displacement agent. The above raw materials are calculated by mass ratio: amphiphilic FAU nanocrystalline fluid: sodium octylphenol polyoxyethylene ether sulfonate: water = 100:1.5:10.

[0020] Example 3

[0021] Step 1: Add (3-(2-aminoethyl)aminopropyl)triethoxysilane to white carbon black and mix well, add sodium aluminate aqueous solution prepared by dissolving sodium aluminate in water, stir well to obtain a gel-like semi-liquid mixture, wherein the above raw materials are calculated by mass ratio of white carbon black: sodium aluminate: (3-(2-aminoethyl)aminopropyl)triethoxysilane: water = 1:1.1:2:10; Step 2: The mixture is transferred into an open glass container under steam-assisted conditions, and the glass container is then transferred into a hydrothermal reactor liner, deionized water is added into the liner, and the mass of the deionized water is 1 times the mass of the mixture, and water outside the glass container is prevented from entering the glass container; the mixture is crystallized at a temperature of 100° C. under steam-assisted conditions for 6 hours to obtain a crystalline product; Step 3: washing the crystal product, drying and calcining the product in sequence, at a calcination temperature of 250° C. for 5 hours, to obtain lipophilic FAU nanocrystals in one step; Step 4: Place a sodium hydroxide aqueous solution (concentration 1.7 g / L) into a round-bottom flask, add ethanol and mix well, add lipophilic FAU nanocrystals, and stir at 75°C for 3 hours to obtain an amphiphilic FAU nanocrystal fluid. The above raw materials are calculated by mass ratio: lipophilic FAU nanocrystals: sodium hydroxide aqueous solution: ethanol = 1:65:34; Step 5: Add the amphiphilic FAU nanocrystalline fluid, disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and water into a round-bottom flask and stir at 85° C. for 3 hours to obtain a temperature-resistant and salt-resistant polyether sulfonate oil displacement agent. The above raw materials are calculated by mass ratio: amphiphilic FAU nanocrystalline fluid: disodium lauryl alcohol polyoxyethylene ether sulfosuccinate: water = 100:3:100.

[0022] Comparative Example 1: Step 1: Place sodium hydroxide aqueous solution (concentration 1.25 g / L) in a round-bottom flask, add ethanol and mix well, add sodium octylphenol polyoxyethylene ether sulfonate, and stir at 85°C for 10 minutes. The above raw materials are calculated by mass ratio: sodium hydroxide aqueous solution: ethanol = 80:20; Step 2: Add the mixed solution prepared in step 1, sodium octylphenol polyoxyethylene ether sulfonate and water into a round-bottom flask and stir at 80° C. for 3 hours. The above raw materials are calculated by mass ratio: mixed solution: sodium octylphenol polyoxyethylene ether sulfonate: water = 100:2.5:1.

[0023] The salt resistance of Example 1 and Comparative Example 1 was tested by standing at 25° C. for 24 hours to observe the effect of different NaCl contents on the solubility of the oil displacement agent as shown in Table 1.

[0024] Table 1

[0025] The temperature resistance of Example 1 and Comparative Example 1 was evaluated under 270°C conditions. The influence of the temperature resistance of the oil displacement agent is shown in Table 2, wherein the initial concentration is based on sodium octylphenol polyoxyethylene ether sulfonate, which is added to the reactor and heated to 270°C under closed conditions for different times. The active substance content is detected by two-phase titration.

[0026] Table 2

[0027] Summary: It can be seen from Table 1 and Table 2 that the oil displacement agent prepared by combining the amphiphilic FAU nanocrystalline fluid with polyether sulfonate in Example 1 is superior to ordinary polyether sulfonate in terms of temperature resistance and salt resistance.

[0028] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a heat-resistant and salt-resistant polyether sulfonate oil-displacing agent, characterized in that: The following steps are involved: Step 1: adding a silane hydrophobic template to white carbon black and mixing them evenly, adding a sodium aluminate aqueous solution prepared by dissolving sodium aluminate in water, stirring evenly to obtain a gel-like semi-liquid mixture, wherein the above raw materials are calculated by mass ratio of white carbon black: sodium aluminate: silane hydrophobic template: water = 1:0.5-2:0.8-2:5-15; Step 2: crystallizing the mixture under steam-assisted conditions to obtain a crystalline product; Step 3: washing, drying and calcining the crystal product in sequence to obtain lipophilic FAU nanocrystals in one step; Step 4: Place a sodium hydroxide aqueous solution with a concentration of 1 to 10 g / L in a round-bottom flask, add ethanol and mix well, add lipophilic FAU nanocrystals, and stir at 70 to 100° C. for 2 to 5 hours to obtain an amphiphilic FAU nanocrystal fluid. The above raw materials are calculated by mass ratio: lipophilic FAU nanocrystals: sodium hydroxide aqueous solution: ethanol = 1:60 to 100:10 to 25; Step 5: Add the amphiphilic FAU nanocrystalline fluid, polyether sulfonate and water into a round-bottom flask and stir at 70-80° C. for 2-5 hours to obtain a temperature-resistant and salt-resistant polyether sulfonate oil displacement agent. The above raw materials are calculated by mass ratio of amphiphilic FAU nanocrystalline fluid: polyether sulfonate: water = 100:1.5-20:0.5-200.

2. The method for preparing a heat-resistant and salt-resistant polyether sulfonate oil-displacing agent according to claim 1, characterized in that: The silane hydrophobic template agent is one of 3-aminopropyltriethoxysilane and (3-(2-aminoethyl)aminopropyl)triethoxysilane.

3. The method for preparing a heat-resistant and salt-resistant polyether sulfonate oil-displacing agent according to claim 1, characterized in that: The polyether sulfonate is one of octylphenol polyoxyethylene ether sodium sulfonate and lauryl alcohol polyoxyethylene ether disodium sulfosuccinate.

4. The method for preparing a heat-resistant and salt-resistant polyether sulfonate oil-displacing agent according to claim 3, characterized in that: Step 2: Crystallizing the mixture under steam-assisted conditions specifically includes the following steps: transferring the mixture into an open glass container, and then transferring the glass container into a hydrothermal reactor lining, adding deionized water to the reactor lining whose mass is 0.5 to 2 times the mass of the mixture, and preventing water outside the glass container from entering the glass container; crystallizing the mixture under steam-assisted conditions at a temperature of 60 to 100° C. for 6 to 12 hours.

5. The method for preparing a heat-resistant and salt-resistant polyether sulfonate oil-displacing agent according to claim 1, characterized in that: The calcination temperature in step 3 is 120-300° C. and the calcination time is 3-6 hours.

6. A heat-resistant and salt-resistant polyether sulfonate oil-displacing agent, characterized in that: The method is prepared by any one of claims 1 to 5.

Citation Information

Patent Citations

  • Preparation method and application of hierarchical zeolite molecular sieve

    CN103073020A

  • Zeolites with hierarchical porosity

    CN105431380A

  • High-silicon Y zeolite and preparation method thereof

    CN108946758A

  • Nano zeolite imidazate framework material, preparation method thereof and application of nano zeolite imidazate framework material in oil displacement

    CN112898588A

  • Nano-surfactant for oil production and method for preparing the same

    CN1544572A